Estudo de liberação de lamotrigina inserida em fibras de Ecovio® - Cândido, Gabriela Braga Gomes (2023)
Epilepsy is a disease caused by an alteration in auditory signals, which can cause fainting and muscle contractions. Thus, one of the medications indicated for the treatment of epileptic seizures is Lamotrigine, classified as class II in the biopharmaceutical classification system, as it has low solubility and high permeability in interstitial fluids. Currently, the pharmaceutical forms currently available for the treatment of epilepsy present high rates of drug interactions and new forms of drug release have been investigated, in which transdermal delivery systems have appeared with great prominence. Therefore, the present work aims to produce polymeric nanofibers using the electrospinning technique, incorporating the drug Lamotrigine into its structure. To this end, the experimental conditions for the production of fibers were evaluated, using the Ecovio® polymer mixture in order to obtain an alternative administration technology to reduce interaction effects and also promote an increase in the solubility of the active ingredient. The membranes produced (15% m/v of Ecovio® in a solution of 85% chloroform: 15% dimethylformamide and with 5%, 10%, 20% and 30% m/m of drug) were prepared by scanning electron microscopy analyzes (SEM), infrared spectroscopy (FTIR), thermogravimetry (TGA), differential scanning calorimetry (DSC), X-ray diffraction (XRD), consistency analysis, conductivity, mechanical analysis, release and permeation study. The release profiles found were adjusted in different release kinetic models, with the Weibull model proving to be the most appropriate, as it is the most commonly used model for presenting drug release profiles in which a polymeric delivery matrix is used of pharmaceuticals. The best lamotrigine concentration obtained was 5%, due to greater release and permeation.